Formulasi Pasta Gigi Minyak Kelapa Murni - Astuty, Meilinda Windy; Yuniarti Z., Panti; Dharmayanti, Luky (Jurnal Kesehatan Rajawali, 2023)
Oral and dental health problems that often occur are dental hard tissue disease (dentinal caries) or dental caries. Dental caries is damage to hard tooth tissue caused by microorganisms. The type of bacteria that can cause plaque on teeth is Streptococcus mutans bacteria. Toothpaste is a mixture of abrasive ingredients that help clean teeth without damaging them. Virgin coconut oil is an oil that comes from coconut fruit and contains high lauric acid and has antibacterial and calcium properties. Virgin coconut oil in this study is an active substance that is formulated into toothpaste preparations. The aim of the study was to formulate and evaluate virgin coconut oil toothpaste preparations. The research method used was an experimental laboratory to obtain yield data. Virgin coconut oil is made by separating coconut cream from skimmed water, so that virgin coconut oil is obtained as an active substance. Toothpaste formulation consists of 3 formulas, namely the concentration of VCO in Formula I 25%, Formula II 30% and Formula III 40%. Evaluation of toothpaste that was carried out was organoleptic test, pH, spreadability, foam formation, stability, and panelists. The results obtained from the evaluation carried out on the three formulas, Virgin coconut oil can be made into toothpaste and variations in the concentration of Virgin coconut oil do not affect the physical properties of the toothpaste. Panelist test on Formula II is more preferable than Formula I and Formula III.